Self-reported strategy use and prospective memory: The roles of cue focality and task importance. - Harrington, Erin E.; Reese-Melancon, Celinda; Turner, Rachael L. (Memory & Cognition, 2025)
Interest in the metacognitive aspects of prospective memory (PM) is growing. Yet, the interplay between participants' metacognitive awareness of PM task demands and features that contribute to successful PM require further attention. To this aim, participants in the current study completed laboratory-based PM tasks of varying difficulty (cue focality: focal, nonfocal-category, or nonfocal-syllable) and reported their strategy use and perceptions of PM task importance. Most participants reported using a strategy regardless of cue focality. However, only under the most challenging condition (i.e., nonfocal-syllable) did participants who reported using a strategy exhibit better PM performance compared to those who did not use a strategy. Additionally, strategy use and cue focality were independently associated with greater costs to ongoing task performance: strategy users exhibited greater slowing relative to individuals who did not use a strategy, and the extent of slowing was greater as the task difficulty increased across cue focality. Finally, perceived task importance appeared to play an important role in the interactive link between cue focality and strategy use on PM performance for the more challenging, nonfocal PM tasks. Specifically, moderation analyses suggested that greater perceived task importance alone may improve the likelihood of PM success for moderately challenging PM tasks (i.e., nonfocal-category), but for the most challenging PM tasks (i.e., nonfocal-syllable), individuals' strategy use was still associated with better PM performance. The present study expands our understanding of metacognition's role in PM performance and has implications for everyday PM performance.